Health Promotion Efforts as Predictors of Physical Activity in Schools: An Application of the Diffusion of Innovations Model. (June 2016) - Glowacki, Elizabeth M.; Centeio, Erin E.; Van Dongen, Daniel J.; Carson, Russell L.; Castelli, Darla M.
ABSTRACT: BACKGROUND: Implementing a comprehensive school physical activity program (CSPAP) effectively addresses public health issues by providing opportunities for physical activity (PA). Grounded in the Diffusion of Innovations model, the purpose of this study was to identify how health promotion efforts facilitate opportunities for PA. METHODS: Physical and health education teachers (N = 256) nationwide were surveyed using a CSPAP Index to identify teacher's efforts for providing opportunities for PA within a school setting. RESULTS: A hierarchical regression analysis revealed total number of PA opportunities was significantly predicted by teachers' health promotion efforts, p < .001. Sex and years of experience were not significant covariates, p = .35, in the final step of the model. Accounting for teaching environments, the model was significant, p < .001. The strongest predictors were the promotional efforts of PA for family and community, p < .001, PA for staff members, p < .01, PA during the school day, p < .05, and PA before school, p < .05. CONCLUSIONS: To increase PA opportunities for children in schools, emphasis should be placed on health promotion. This study confirms the importance of teachers involving family, community, and staff members as co‐health promoters when trying to increase PA engagement surrounding schools.